Studying the heritage of leaders of Alash in the years of independence - Smagulov, Zh.K.; Kalybekova, K.S.; Bazhikeev, K.K. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The independence of our country is the beginning of our new national history. The current course of our state, as well as other sciences, has set a huge task for the national literary science. One of them is the study of the heritage of leaders of Alash who were subjected to innocent slander. In order to fulfill this task, literary scientists aimed to compensate for the shortcomings of the history of national literature, to bring literary personalities who were subjected to wrongful punishment back to the stage of history, to put them on the pedestal of justice and to evaluate the worthy place of each person in the history of literature. The article examines the research works of Kazakh literary critics who studied and analyzed the literary heritage of leaders of Alash from the moment of independence to the present day, evaluates and analyzes the research of Kazakh literary critics who contributed to the study of the literary heritage of leaders of Alash during the period of independence. In this study, the main features of the works published during the years of independence, which dealt with various issues in the life and work of such personalities as A. Bokeikhan, A. Baitursynov, Zh. Aimauytuly, M. Zhumabaev, and others were studied, and cognitive and thematic channels were determined. The opinions and views of literary critics about the leaders of Alash were differentiated in terms of the requirements of the new time. The sources considered in the research work are monographs and textbooks, research articles by literary critics S. Qirabaev, T. Kakishev, R. Nurgali, Sh. Eleukenov, O. Abdimanuly, R. Turysbek, M. Absemetov, A. Ismakova, S. Aqqululy, Zh. Smagulov, and others who purposefully studied the literary and scientific heritage of the leaders of Alash.
Keywords: independence; literary studies; leaders of Alash; literary heritage; A. Bokeikhan; A. Baitursynov; M. Zhumabaev.